CONCEPTION OF SCIENCE AND SCIENTIFIC METHOD IN PSYCHOLOGY STUDENTS - Granados, Elisabeth Elodia (2013)
Specific research on the concept of psychology has indicated that one of its essential attributesis its scientific nature. Access to the concepts of science and the scientific method with a socialcollective approach facilitates understanding the cognitive representations of the assumptions thatunderlie and determine aspecific manner of performing an act.. We conducted this research with169 Psychology students and each received the Natural Semantic Networks. In-depth interviewsand questionnaire were used to clarify the science and scientific method foundations presented by students during three stages of their formation (beginning, middle and end). Respecto al métodocientífico, se destaca la incorporación de terminología específica y alusiones a procedimientosmetodológicos, según corrientes teóricas de la Psicología.The results show little variations of theconcept of science presenting a strong imprint/impronta of the traditional model. As concernsthe scientific method, the inclusion of specific terminology is underscored as well as referencesto methodological procedures, according to theoretical schools of thought on psychology. Theresearch provides conceptual elements to encourage the professors to think about how to teachskills in order to conduct research in the area of psychology.